Efficacy of Dentaq® Oral and ENT Health Probiotic Complex on Clinical Parameters of Gingivitis in Patients Undergoing Fixed Orthodontic Treatment: A Pilot Study - (:unkn) unknown (My University, 2016)
OBJECTIVES: Probiotics act as a unique approach to maintaining oral health by supplementing the endogenous oral bacteria with additional naturally occurring beneficial microbes to provide defense against pathogens harmful to teeth and gingiva. The aim of this pilot study was to clinically evaluate the effects of probiotics on plaque accumulation and gingival inflammation in subjects with fixed orthodontics. METHODS: The pilot study was comprised of 15 healthy patients, aged 11 to 18 years, undergoing fixed orthodontic treatment. Patients used an all-natural, dissolving lozenge containing six proprietary probiotic strains (Dentaq® Oral and ENT Health Probiotic Complex)for 28 days. Gingival Index (GI) according to Löe-Silness and Plaque Index (PI) according to Quigley-Hein for all teeth were measured at baseline (Day Zero) and at the end of the probiotic regimen (Day 28). RESULTS: The mean baseline GI and PI scores within each patient decreased by 28.4% and 35.8%, respectively, by Day 28. Patients reported decreased tooth and gingival pain, decreased oral bleeding, and increased motivation to maintain proper oral hygiene over the course of the study. CONCLUSIONS: This pilot study provided preliminary support for the use of Dentaq Oral and ENT Health Probiotic Complex as a safe and effective natural health product for the reduction of plaque accumulation and gingival inflammation. The results demonstrate its potential therapeutic value and open the door for larger scale placebo-controlled clinical studies to verify these findings.
Keywords: Female; Humans; Adolescent; Male; Child; Pilot Projects; Periodontal Index; Probiotics; Gingivitis; Dental Plaque Index; Dental Plaque; Orthodontics; Gingival index; Plaque index